Carrot Intake its Perception, Nutritional Value and Health Benefits: A Case Study of Sokoto Metropolis, Sokoto State, Nigeria - Fabiyi, E.F.; Abubakar, B.Z.; Yahaya, A.T.; Yakubu, A.A.; Yakubu, D.H. (Pakistan Journal of Nutrition, 2015)
The investigation on carrot intake, its perception, nutritional value and its health benefits was conducted in Sokoto Metropolis, Sokoto State, Nigeria. Purposive sampling techniques were used to select Sokoto Metropolis (two local government areas) and twelve wards from two LGAs. Simple random sampling technique was used to select 120 people from the study area. Interview schedule was also employed to seek information from the selected people on demographic characteristics, carrot eating, perception about importance of carrot eating and the diseases that are common among the people. The data collected were analyzed using descriptive statistics and chi-square. The result revealed that some demographic characteristics such as sex, age, occupation and educational status have influence on carrot intake. Also the findings revealed that majority (46 and 44%) agreed that regular eating of carrot improve their health and only 2% disagreed, while 8% had no idea about the health benefits. Chi-square test revealed that there is significant difference between intake of carrot during production season and during off-season. The result revealed that some food related diseases are common in the study area. About 50% did not indicate the diseases they were suffering from. Among those who indicated their diseases; 14% were suffering from poor eyesight, 9% had skin disease, 8% had ulcer, 7% suffering from hypertension, 4% had painful urination, 4% had gum disease and another 4% were suffering from diabetic condition. It can be concluded that nutritional education about the food we consume, awareness and information about the importance of regular intake of carrot may change the wrong perception of the people about carrot consumption in relation to health benefits. Awareness campaign about the importance of carrot consumption should be done by government and extension workers.